PENGUKURAN KINERJA KEUANGAN BERDASARKAN ROI (RETURN ON INVESTMENT) DENGAN PENDEKATAN SISTEM DUPONT PADA PT. TROPICA COCOPRIMA - Daud Steven Landora’i; Recky Rengkung .,; Ellen Tangkere ., (Sam Ratulangi University, 2017)
The purposes of this study are: (1) to analyze financial performance at PT. Tropica Cocoprima based ROI (Return On Investment) with Dupont system approach in the period 2012-2014 year, (2) Comparing the ROI (Return On Investment) on PT. Tropica Cocoprima year period 2012-2014. This study will be conducted at PT. Tropica Cocoprima which is housed in the City Hall No. 12 Manado. This study was conducted over two months, from the month of September until the month of October 2016. This study uses secondary data to be retrieved directly from the company PT.Tropica Cocoprima. Methods of data collection in this research with the study documentation in the form of financial statements of income and balance period of 2012, 2013 and 2014. The data are taken from the financial statements is the data that supports the measurement of ROI (Return On Investment), such as cost of goods sold , cost of sales, administrative expenses, tax, sales, cash, bank, accounts receivable, inventory and fixed assets. In this study, analysis of the data used is quantitative analysis by performing the calculation of ROI (Return On Investment). Regarding these calculations in this study will be conducted by a systems approach Dupont. This study emphasizes the use of data in the form of numbers that is processed and analyzed to obtain conclusions about the picture of the financial performance of the company PT. Tropica Cocoprima. Dupont system is basically used to be able to evaluate the effectiveness of the company to see how the company's return on investment. In Dupont analysis needs to be calculated: ratio of activity and profitability. Based on the results of measurements of financial performance using Dupont analysis shows that during the period 2012-2014: (1) The financial performance of PT. Tropica Cocoprima based on Return On Investment (ROI) with Dupont System Analysis approach can be said to be in stable conditions, although less stable companies still able to produce a return on the investment made. Rise and fall of Return On Investment (ROI) is caused by the rise and fall of the Net Profit Margin (NPM), Net Profit Margin (NPM) in unfavorable conditions due to net income experienced a significant decline, the decline in net income is affected by total cost increased, this increase occurred due to the increase of cost of sales, especially in the purchase of raw materials is very large. while Total Assets Turn Over (TATO) in good condition because increased during the years 2012-2014. (2) The calculation Systems Analysis Dupont also show that the percentage of Return On Investment (ROI) in 2013 better than the percentage level Return On Investment (ROI) in 2012 and 2014, and the percentage rate of return on investment in 2012 better compared Return on Investment (ROI) in 2014.